Digital humanities approaches to analyzing indonesian language texts as non-western languages - Rastya Mutiarani Zahra (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This research explores the integration of digital humanities methods in the analysis of Indonesian language texts to enhance linguistic and cultural understanding. The primary objective is to develop tailored digital humanities methodologies, applying computational tools such as text mining, natural language processing, and corpus linguistics to analyze linguistic and thematic patterns within Indonesian texts. By leveraging these techniques, the study aims to provide new insights into language use, cultural narratives, and historical shifts in Indonesia. A qualitative approach, including a literature review and case studies, is used to examine existing research and methodologies, and assess how digital tools can be effectively applied in this context. The study also addresses the accessibility of Indonesian textual data for researchers, educators, and students, proposing solutions to make these resources more usable and integrated into the global digital humanities framework. This research contributes to expanding the scope of digital humanities by incorporating Indonesian language texts, offering a model for future studies in non-Western linguistic traditions.